Points to consider when developing drugs for dry eye syndrome - Suyoung Bae; Hosun Seung; Ho Jung Oh (Osong Public Health and Research Perspectives, 2023)
Changes in both the social environment (e.g., the increased use of electronic media) and the atmospheric environment (e.g., air pollution and dust) have contributed to an increasing incidence of eye disease and an increased need for eye care. Notably, the signs and symptoms of dry eye syndrome can impact the daily quality of life for various age groups, including the elderly, and usually requires active treatment. The symptoms of dry eye syndrome include tear film instability, hyperosmolarity, ocular surface inflammation and damage, and neurosensory abnormalities. As treatments for dry eye are being developed, a standardized guideline is needed to increase the efficiency of drug development and improve the quality of clinical trial data. In this paper, we present general considerations for the pharmaceutical industry and clinical trial investigators designing clinical trials focused on the development of drugs to treat dry eye syndrome.